2003
DOI: 10.1021/jp0278566
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Dependence of Mn2+ Luminescence in Differently Sized ZnS:Mn Nanoparticles

Abstract: The pressure behavior of Mn2+ emission in the 10-, 4.5-, 3.5-, 3-, and 1-nm-sized ZnS:Mn2+ nanoparticles is investigated. The emission shifts to lower energies with increasing pressure, and the shift rate (the absolute value of the pressure coefficient) is larger in the ZnS:Mn2+ nanoparticles than in bulk. The pressure coefficient increases with the decrease in particle size with the 1-nm-sized particles as an exception. Pressure coefficient calculations based on the crystal field theory are in agreement with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…However, some other groups reported that the lifetime of Mn 2+ luminescence was in the millisecond range [34,49,86,87] while attributing the fast decay component in the nanosecond range to ZnS defect emission. Their results show that the nanosecond decay times reported for the Mn 2+ emission are most likely because the tail of broad defect related ZnS emission which overlaps with Mn 2+ emission at around 590 nm.…”
Section: Shortening Of Emission Lifetimementioning
confidence: 99%
See 3 more Smart Citations
“…However, some other groups reported that the lifetime of Mn 2+ luminescence was in the millisecond range [34,49,86,87] while attributing the fast decay component in the nanosecond range to ZnS defect emission. Their results show that the nanosecond decay times reported for the Mn 2+ emission are most likely because the tail of broad defect related ZnS emission which overlaps with Mn 2+ emission at around 590 nm.…”
Section: Shortening Of Emission Lifetimementioning
confidence: 99%
“…As the particle size reduced, the shift between the absorbing and emitting state increased. Su et al [86] studied the absorption (ABS) spectrum of the 3.5 nm ZnS:Mn 2+ particles sample, whose absorption edge is at 335 nm with an absorption peak at 310 nm which is about 30 nm blue-shift from the absorption of bulk ZnS:Mn 2+ at 342 nm as a result of quantum size confinement.…”
Section: Blue-shift Of Abs and Ple Spectrummentioning
confidence: 99%
See 2 more Smart Citations
“…Impurities in semiconductors have attracted a great deal of attention for many years owing to their significance for practical applications, as in photoconductors, microwave detectors, and electroluminescent devices [1][2][3][4][5][6][7][8]. Among the impurities, particular attention has been focused on the transition metal ions because they are commonly associated with deep levels within the host crystal band gap.…”
Section: Introductionmentioning
confidence: 99%